Do the globalization and imports of capital goods from EU, US and China determine the use of renewable energy in developing countries?. Issue 1 (31st December 2023) - Liu, Zhe; Ahmad, Imtiaz; Perveen, Zainab; Alvi, Shahzad
Abstract: The developing countries rely heavily on imports of capital goods to spur economic growth. When the economy grows, energy consumption rises, adversely impacting climate change. The low levels of renewable energy share in total energy consumption, developing nations confront a difficult task in achieving the SDGs targets related to an increase in renewable energy share and access to affordable, reliable, and modern energy. Finding solutions to increase renewable energy usage is critical. International trade is an unavoidable part of development, prompting us to consider the impact of imports on renewable energy usage. This study explores the effects of imports of capital goods from China, EU and USA on renewable energy consumption in developing countries by using panel data from 20 countries spanning 2000–2018. It is found that capital goods imported from China in developing countries negatively impact renewable energy consumption while imports from EU have a positive impact on renewable energy consumption. However, in the case of US it is found negative but insignificant. The role of economic, social, and political globalization is explored, and it is found that three types of globalization are positively and significantly linked with renewable energy consumption. Thus, this study recommends that trade policies complement domestic efforts toward increasing renewable energy production and consumption in developing countries.